2007
DOI: 10.1111/j.1651-2227.2007.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding outcomes for mothers with and without home access to e‐technologies

Abstract: A vast majority of breastfeeding mothers have home access to e-technologies in France. However, access to e-technologies was not independently associated with better breastfeeding outcomes in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 20 publications
(19 reference statements)
0
24
0
Order By: Relevance
“…), with more women in the usual care group than the e‐technology group having a BAS < 8 (Laborde et al . ). However, there was no significant difference between the e‐technology and usual groups in BF intention scores ( P > 0.05) (Scott ), coping with BF scores (Hannula et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…), with more women in the usual care group than the e‐technology group having a BAS < 8 (Laborde et al . ). However, there was no significant difference between the e‐technology and usual groups in BF intention scores ( P > 0.05) (Scott ), coping with BF scores (Hannula et al .…”
Section: Resultsmentioning
confidence: 97%
“…One study (Laborde et al . ) assessed BF assessment using a 5‐item 3‐point BF assessment score (BAS) with a BAS < 8 indicating a women was at risk of early weaning (Hall et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salonen, Kaunonen, Astedt-Kurki, Jarvenpaa, and Tarkka (2008) examined an Internet-based breastfeeding intervention for parents of newborn infants and found that participants scored significantly higher in positive attitude and behavioral intention toward breastfeeding. Similarly, Laborde et al (2007) discovered that young French mothers of newborn babies with access to e-technologies reported significantly higher breastfeeding duration than those without access. As such, in order to increase future breastfeeding intention, it is important to first increase knowledge and positive beliefs about the subject.…”
Section: Theoretical Frameworkmentioning
confidence: 95%
“…The home access to e-technologies was evaluated by Laborde et al 94 in France. They noted that women with available technologies were more apt to be employed, did not use pacifiers, and did not smoke.…”
Section: Practical Management Of the Mother-infant Nursing Couplementioning
confidence: 99%